2021
DOI: 10.1080/17512433.2021.1961577
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination and their importance for lung transplant recipients in a COVID-19 world

Abstract: Introduction: Lung transplant patients are immunocompromised because of the medication they receive to prevent rejection, and as a consequence are susceptible to (respiratory) infections. Adequate vaccination strategies, including COVID-19 vaccination, are therefore needed to minimize infection risks.Areas covered: The international vaccination guidelines for lung transplant patients are reviewed, including the data on immunogenicity and effectivity of the vaccines. The impact on response to vaccination of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 95 publications
0
11
1
Order By: Relevance
“…Vaccination against COVID-19 is an essential step in the prevention of severe COVID-19 infection in LuTx recipients ( 28 ). Currently, LuTx candidates are recommended to undergo vaccination while on the transplant waiting list ( 5 , 21 ). These recommendations stem from the fact that the COVID-19 vaccine immunogenicity, efficacy and safety were shown to be greater in the pre-transplant patients as compared to the SOT recipients ( 5 , 8 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vaccination against COVID-19 is an essential step in the prevention of severe COVID-19 infection in LuTx recipients ( 28 ). Currently, LuTx candidates are recommended to undergo vaccination while on the transplant waiting list ( 5 , 21 ). These recommendations stem from the fact that the COVID-19 vaccine immunogenicity, efficacy and safety were shown to be greater in the pre-transplant patients as compared to the SOT recipients ( 5 , 8 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been already demonstrated that patients that were vaccinated while on the transplant waiting list were able to mount much higher anti-SARS-CoV-2 immune responses as compared to patients that were vaccinated after the transplantation ( 5 , 21 ).…”
Section: Anti-covid-19 Vaccination In Lung Transplant Recipients: Fir...mentioning
confidence: 99%
See 2 more Smart Citations
“…Transplant patients are immunosuppressed and at increased risk of morbidity and mortality related to infection as compared to the immunocompetent population. This increased risk profile also holds true for coronavirus disease 2019 (COVID-19) infection [ 1 – 4 ]. Vaccination is an important strategy to prevent post-transplant complications.…”
Section: Introductionmentioning
confidence: 99%